Climate change mitigation on tropical peatlands: A triple burden for smallholder farmers in Indonesia. (November 2021) - Merten, Jennifer; Nielsen, Jonas Østergaard; Rosyani,; Faust, Heiko
Highlights: Climate mitigation policy led to a paradigmatic shift in peatland management. Transnational actor networks influence peatland governance in the Global South. Smallholder farmers are negatively affected by international climate mitigation policy. Peatland mitigation action fails to integrate important justice components. Abstract: The agricultural use and conversion of tropical peatlands is considered a major source of land-based greenhouse gas emissions. Thus, the protection and restoration of tropical peatlands has recently turned into an important strategy to mitigate global climate change. Little research exists that has investigated the impacts and dynamics that such climate mitigation efforts evoke in local communities living in and around peatlands. We present insights on this from Sumatra, Indonesia and use a climate justice lens to evaluate local outcomes. We show how an increasingly transnational network of state and non-state actors has become involved in developing new laws, policy programs and land-use agreements on Sumatra's coastal peatlands, aiming at supposedly win–win low-carbon development pathways. We argue that such efforts are open to much of the same criticism that has been raised regarding previous policies and projects aimed at reducing GHGE from deforestation and forest degradation. These projects disregard local perspectives on development, fail to deliver the promised benefits and, through a reconfiguration of local land-use rights, reduce the capabilities of smallholder farmers to benefit from their land. In sum, our analysis suggests that recent policies and projects aimed at mitigating GHGE from tropical peatlands contribute to a redistribution of the global climate mitigation burden onto smallholder farmers in Indonesia. This occurs through their threefold assignment to protect forests, prevent fires and help restore degraded peatlands.